Adaptive Stream Processing with Reinforcement Learning: Optimizing Real-Time Data Pipelines (Global Journal of Computer Science and Technology, 2025)
This article explores the integration of Reinforcement Learning RL with stream processing systems to address the fundamental challenges of handling unpredictable workloads and dynamic resource constraints Traditional stream processing frameworks rely on static configurations that struggle to adapt to fluctuating conditions leading to either resource over provisioning or performance degradation The article presents RL as a promising solution through intelligent agents that continuously learn from system performance to optimize crucial parameters including task scheduling resource allocation checkpoint frequency and load balancing It examines the critical importance of adaptivity in stream processing outlines RL fundamentals applicable to this domain and details specific applications including dynamic resource allocation task scheduling optimization adaptive check pointing and intelligent load balancing Additionally it addresses implementation challenges such as training overhead reward function design cold start problems and integration with existing frameworks Current tools and frameworks enabling RL-enhanced stream processing are evaluated and future research directions including multi-agent RL federated reinforcement learning explainable RL for operations and green computing optimization are discussed
Keywords: : reinforcement learning; stream processing; adaptive computing; resource optimization; distributed systems